Responsive Law as a Social Control Concept for Digital Society in Protecting Personal Data Against the Use of ChatGPT - Suwandoko; Yusticia Dewi Maharani; Haerudin; Eni Setyo Susilowati; Rini Fidiyani; Suhadi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Misuse of personal data in the use of ChatGPT, there is a leak of personal data in Indonesia as many as 2,555 accounts. The need for the role of law as a means of social control to emphasize how law can function adaptively in a digital society, thereby providing new contributions in the formulation of personal data protection strategies amidst the advancement of artificial intelligence, especially ChatGPT. The purpose of this study is to analyze the sociological study of law on the phenomenon of digital society in the use of ChatGPT and analyze how to overcome the phenomenon of artificial intelligence exploitation in the misuse of personal data in the use of ChatGPT. The type of research used in this study is normative juridical. That the sociology of law has the meaning as a law that responds to the phenomenon of the use of ChatGPT, legal sociology plays a role in protecting public interests and maintaining justice. Referring to the development of digital technology and the increasingly widespread use of ChatGPT in people's lives, serious problems arise regarding the protection of personal data that is vulnerable to misuse. In this context, responsive law is relevant because it offers openness to adapt to social dynamics and answers the needs of the digital society. As a tool of social control, the law plays a role not only in maintaining security and order, but also in ensuring that people's rights are protected amidst the flow of technological transformation.